IN VIVO STUDY OF WOUND-HEALING ACTIVITY OF POLYSACCHARIDE GEL WITH ENCAPSULATED SEA-BUCKTHORN OIL (HIPPOPHAE RHAMNOIDES) - M.A. OLIMOV; M.U. SHAROFOVA; F.M. KHODZHAEVA; A.D. KHOLBEKOV; J.T. BOBOKALONOV (Паёми Сино, 2023)
Objective: To study the morphophysiological features of burn wound healing in rats using a polysaccharide gel form based on pectin and polysaccharide from apricot gum with encapsulated sea buckthorn oil.